-2x+1=2(x-4)

Simple and best practice solution for -2x+1=2(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+1=2(x-4) equation:


Simplifying
-2x + 1 = 2(x + -4)

Reorder the terms:
1 + -2x = 2(x + -4)

Reorder the terms:
1 + -2x = 2(-4 + x)
1 + -2x = (-4 * 2 + x * 2)
1 + -2x = (-8 + 2x)

Solving
1 + -2x = -8 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
1 + -2x + -2x = -8 + 2x + -2x

Combine like terms: -2x + -2x = -4x
1 + -4x = -8 + 2x + -2x

Combine like terms: 2x + -2x = 0
1 + -4x = -8 + 0
1 + -4x = -8

Add '-1' to each side of the equation.
1 + -1 + -4x = -8 + -1

Combine like terms: 1 + -1 = 0
0 + -4x = -8 + -1
-4x = -8 + -1

Combine like terms: -8 + -1 = -9
-4x = -9

Divide each side by '-4'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| 3f-80+25+10k= | | 2/s=3/18 | | 3G+50+2g=125 | | 7/5(-35)+11 | | 5w^(-1/3)=3 | | 9x^2-a^2=0 | | v/15=4/6 | | -5y=-4x+16 | | 7-3x=6+5x | | 1/x=5/30 | | 3*x^2-4*x+9=0 | | (2x-1)(4x/1) | | -4x-3=x-8 | | 1/x=530 | | 12x-14x+4=0 | | 11/18+7/8 | | 2/b=8/12 | | 200x+3200=20 | | 32*x=137.5 | | 54/9-7/15 | | 7x+1=6/x | | 3x=y+12 | | .3+.15m=13.5 | | 5x^2+14=0 | | -4/3x-4/5=-1/2 | | 7/x+1=6/x | | Y=2*-10-6 | | -9/2=-3/2w+3/5 | | 15w-9=7w+7 | | 2(x-6)=x+5 | | -1/2v-6/5=-2/3 | | 2*x^2-12*x-1=-7*x+6 |

Equations solver categories